The Effect of Interaction of Microbially Immobilized Biochar and Salinity Stress on Soil Chemical Properties (pH, EC, C-organic, and CEC) in Red Spinach (Amaranthus tricolor L.) Cultivation - Nofia Wahyu Puspita; Rossyda Priyadarshini; Fitri Wijayanti (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Soil salinity reduces nutrient availability and inhibits plant growth. While red spinach (Amaranthus tricolor L.) exhibits tolerance to suboptimal conditions, its growth declines significantly under high salinity stress. This study evaluated the efficacy of microbially immobilized biochar in ameliorating the chemical properties of saline-stressed soil and enhancing red spinach growth. The experiment employed a Completely Randomized Design (CRD) with two factors: biochar dose (0, 15, 30, and 45 t ha⁻¹) and NaCl salinity levels (0, 4, 6, and 8 mS cm⁻¹), with three replications totaling 48 experimental units. Soil parameters measured included pH, electrical conductivity (EC), organic carbon (C), and cation exchange capacity (CEC) at 0 and 28 days after planting (DAP), while fresh plant weight was recorded at 28 DAP. Data were analyzed using ANOVA followed by a 5% Least Significant Difference (LSD) test. Results indicated that biochar application significantly influenced soil pH and CEC. The 30 t ha⁻¹ treatment yielded the highest pH (7.31) at 28 DAP, whereas the 45 t ha⁻¹ treatment achieved the maximum CEC (61.84 cmol kg⁻¹). NaCl stress significantly increased soil EC from 0.93 to 8.69 mS cm⁻¹ at the highest dose, while organic carbon remained unaffected by either treatment. Although the 15 t ha⁻¹ dose was optimal for pH improvement and the 45 t ha⁻¹ dose for CEC enhancement, the 45 t ha⁻¹ treatment overall proved most effective in improving the chemical properties of saline soil and supporting red spinach growth, maintaining stable pH, EC, CEC, and organic carbon values through 28 DAP.